ROTASI MANDATORY SEBAGAI PEMODERASI PENGARUH NON AUDIT SERVICES, AUDIT TIME BUDGET PRESSURE PADA INDEPENDENSI AUDITOR - Listya Dewi, I Gusti Ayu Dwi; Dharma Suputra, I Dewa Gede (E-Jurnal Akuntansi, 2017)
This study intends to obtain empirical evidence regarding mandatory rotation as the moderating influence of non-audit services and audit time budget pressure on auditor independence. This research was conducted at the Bali Provincial Public Accountant Office, which is registered in the Directory Institut Akuntan Publik Indonesia (IAPI) 2016. Using questionnaire technique survey method and 42 auditors as the population in this study that working in the Bali Provincial Public Accountant Office. This Study using sampling method non probability with saturated sampling technique. Analysis of the data used is Moderating Regression Analysis (MRA). The results of the analysis showed that the non-audit services have a negative effect on the independence of auditors, audit time budget pressure negatively influence the independence of the auditor, mandatory rotation weaken the influence of non-audit services on auditor independence. Mandatory rotation of audit time budget strengthens the influence of pressure on auditor independence.
Keywords: non-audit services, audit time budget pressure, mandatory rotation, auditor independence